A Cross-Sectional Study of General Nutrition Knowledge among Nursing Students in the UAE - Rasha A. K. Ibrahim; Aisha N. Aldawsari (Journal of Nutrition and Metabolism)
Background. Adolescence is a crucial time for establishing long-lasting healthy habits, but many university students often engage in unhealthy eating behaviors. Increased independence, social influences, and mental stress all play a role in leading to poor dietary choices that can impact overall health and well-being. It is important to have a good grasp of nutrition to make informed food choices and avoid the development of chronic illnesses. Purpose. To assess the nutrition knowledge of nursing students and examine the interconnections between participants’ beliefs about diet, disease, and weight management Methods: A total of 100 nursing students participated in this descriptive cross-sectional study. Data gathering was conducted from March 2023 to May 2023 at a nursing college in the UAE. Participating students completed a self-reported validated revised general nutrition knowledge questionnaire (GNKQ-R). Descriptive statistics and Pearson’s correlation were used for analysis, along with univariate and multivariate analyses as a statistical methodology to examine individual variables within the dataset independently. Cronbach’s alpha coefficient of the scale in this study is 0.880. A cut-off point of 50 percent correctness was employed to signify a high level of knowledge. Results. All participating students were female, with the majority (94%) being single. Most students (68%) had a normal mass index of 23.6, whereas 32% were overweight. The analysis showed that more than half of the students (57%) rated their overall health condition as good. The analysis also found that the only variable detected to predict the good nutrition knowledge level among studied students was having children less than 18 in the same family. Conclusion. The results of the current study indicate that future wellness actions should prioritize increasing students’ general nutrition knowledge while also considering individual and academic factors impacting NK in college.